Finite element simulation of arrays of hollow spheres structures - Amani, Yasin (2014)
The numerical simulation of a repetitive model of a cellular metal is developed for fundamental investigation of elastic behaviour of hollow sphere structures. Syntactic and partial morphologies of simple cubic configurations of hollow sphere structures are prescribed under boundary conditions corresponded to unit cell and whole hollow sphere lattice. Based on the proposed plotted diagram consists of relative Young’s modulus versus relative density it is possible to explain behaviour of hollow sphere structure with any size and shape disregarded to its basic elastic properties.